Synthesis of Tin Oxide Thin Layer by Doping Aluminum, Fluorine, and Indium Using Sol-Gel Spin Coating Technique - Aris Doyan; Susilawati Susilawati; Lalu Muliyadi (Jurnal Penelitian Pendidikan IPA, 2021)
The synthesis of tin oxide thin films with doping aluminum, fluorine, and indium (SnO2: Al + F + In) by sol-gel spin coating technique has been successfully carried out. This synthesis aims to determine the quality of the thin film formed by adding doping aluminum, fluorine, and indium. The basic material used is SnCl2.2H2O, while the doping material used is AlCl3, NH4F, and InCl3.4H2O. The comparison of the basic ingredients and doping mixture of aluminum, fluorine and indium (SnO2: Al+F +In) used were 100: 0%, 95: 5%, 90: 10%, 85: 15%, 80: 20% and 75: 25%. The synthesis uses a glass substrate with size (10 x 10 x 3) mm. Coating synthesis includes substrate preparation, sol-gel making, film making, and sample heating. The layers that are made consist of 1 to 4 layers. The results showed that the layer formed had a high degree of transparency along with the increasing concentration of the doping material percentage. The higher the doping concentrations of aluminum, fluorine, and indium, the higher the transparency of the resulting layer. Besides, the greater the number of layers, the lower the transparency level of the layers